System for Identifying Pests and Diseases in Soybean Crop through Natural Language - Roque e Faria, Carolinne; de Barbosa, Cinthyan Renata Sachs Camerlengo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The presence of technologies in the agronomic field has the purpose of proposing the best solutions to the challenges found in agriculture, especially to the problems that affect cultivars. One of the obstacles found is to apply the use of your own language in applications that interact with the user in Brazilian Agribusiness, which would bring gains in time, money and accuracy of the analyzes to be performed. This paper proposes the use of Natural Language Processing techniques for the development of an effective system to assist in the identification of pests and diseases in the soybean crop, stored in a database repository to facilitate access to information and diagnosis of the professional.